Foreign exchange interventions under inflation targeting: the Czech Experience - Tomáš Holub (Deutsche Bank Research, 2004)
This paper discusses the role of foreign exchange interventions in the inflation-targeting regime, focusing on the Czech experience since 1998. It concludes that the case for foreign exchange interventions is not clear in an inflation targeting regime both from the theoretical and empirical point of view. First, the stylised facts on the effectiveness of Czech interventions suggest that sometimes these might have had an effect lasting up to 2 or 3 months, but no strategy can be identified that would work in all episodes. Moreover, even many of the "successful" interventions were not able to prevent quite prolonged periods of exchange rate overvaluation in 1998 and in 2002. Second, the sterilisation costs of interventions are shown to have been quite substantial in the Czech Republic, which had in certain period affected their credibility and effectiveness. Third and most importantly, the interventions may lead to tensions with the philosophy of the inflation targeting regimes on the procedural and communication level, which might have a negative impact on the credibility of the policy regime. The paper proposes some criteria for assessing whether the interventions are not in a conflict with the inflation targeting regime, and applies these criteria to the Czech case. From an ex post view, all the intervention episodes are judged to be consistent with the inflation targets and output developments, but there may be some doubt in other respects concerning the intervention episodes in early-1998 and late-1999.
Keywords: E44; F31; E42; E65; E58; E52; 330; Exchange rate; foreign exchange interventions; inflation targeting; sterilisation; Wechselkurspolitik; Inflation Targeting; Wirtschaftspolitische Wirkungsanalyse; Tschechische Republik